Liquor licences issued to Australian schools - Ward, B.; Kippen, R.; Munro, G.; Buykx, P.; McBride, Nyanda; Wiggers, J.; Clark, M. (BioMed Central Ltd, 2017)
Background: Children's positive socialisation to alcohol is associated with early initiation of drinking and alcohol-related harm in adult life. Internationally, there have been reports of adults' alcohol consumption at school events in the presence of children. The aim of this research was to identify the conditions under which Australian schools are required to apply for a liquor licence and the associated prevalence of liquor licences for these events where children were likely to be present. Methods: A document review was conducted to examine temporary liquor licensing legislation. Quantitative analysis was used to examine relevant licensing data. Coding criteria was developed to determine school type, student year levels and the likely presence of children. Results: Four jurisdictions provided data on 1817 relevant licences. The average annual licences/100 schools was highest amongst Independent schools followed by Catholic and public (government) schools. The rates were highest in Queensland and Victoria where children were present at 61% and 32% of events respectively. Conclusions: While there are legislative differences across jurisdictions, the prevalence of adults' alcohol use at school events in the presence of children may reflect the various education department policies and principals' and school communities' beliefs and attitudes. Licences are not required for all events where liquor is consumed so the prevalence of adults' use of alcohol at school events is likely to be higher than our analyses imply. Such practices may undermine teaching about alcohol use in the school curriculum and health promotion efforts to develop alcohol-free events when children are present.